Analysis of the Creative Thinking Process of Kineesthetic Students in Solving Arritmatic Sequences and Series Problems with the Help of Congklak Media Based on Wallas Stages - Nuranita Adiastuty; Budi Waluya; Iwan Junaedi; Masrukan Masrukan; Evi Herayani; Nunu Nurhayati (Universitas Negeri Semarang, 2022)
This study aims to describe the creative thinking process of kinesthetic students in solving arithmetic sequences and series problems with the help of congklak media based on the Wallas stages. The research method used is descriptive qualitative. The subjects of this study consisted of four students of class XI MIPA 5 SMAN 3 Kuningan who were selected using a purposive sampling technique based on the highest kinesthetic learning style questionnaire score. Data was collected through questionnaires, tests, interviews, and observations. The triangulation used is time and technique triangulation. The results showed that: (a) at the preparation stage the four subjects were able to identify problems carefully, completely, and accurately; (b) at the incubation stage, one subject asked the researcher about the concept of an arithmetic sequence, this activity is a stage where the subject looks for a relationship between the concept of an arithmetic sequence and the information contained in the problem so that the subject is able to generate other solutions that are different from what the three thinkers think. another subject; (c) at the illumination stage, the four subjects have a strong will and effort to find alternative solutions to the problems given; and (d) at the verification stage, two subjects were able to get more than one alternative answer idea for each given question, while the other two subjects had not been able to find alternative ideas/other solutions to some of the questions given.